Natural Killer Cells Offer Differential Protection From Leukemia in Chinese Southern Han - Deng, Zhihui; Zhao, Jun; Cai, Siqi; Qi, Ying; Yu, Qiong; Martin, Maureen P.; Gao, Xiaojiang; Chen, Rui; Zhuo, Jiacai; Zhen, Jianxin; Zhang, Mingjie; Zhang, Guobin; et al. (Frontiers in Immunology, 2019)
The interaction of natural killer (NK) cell inhibitory receptors with polymorphic HLA class I molecules educates NK cells for immune surveillance against tumor cells. The KIR A haplotype, which encodes distinct NK cell inhibitory receptors that bind certain HLA-A, -B and -C allotypes, is unusually frequent in East Asians. Focusing on Chinese southern Han, we analyzed 472 acute lymphoblastic leukemia (ALL), 433 acute myeloid leukemia (AML), 193 chronic myeloid leukemia (CML) patients, and 745 healthy controls. We observed a higher frequency of KIR A homozygosity in the healthy controls than in all the leukemia patients combined (OR=0.7, 95% CI=0.6-0.9, P=0.0007). This trend was reflected in each of the subtypes of leukemia studied: ALL (OR=0.7, 95% CI=0.5-0.8, P=0.001), AML (OR=0.75, 95% CI=0.6-0.9, P=0.02), and CML (OR =0.80, 95% CI=0.6-1.1, ns). For ALL, the protective effect of the KIR AA genotype was greater in the presence of KIR ligands C1 and Bw4 (Pc=0.0007), which exhibit strong linkage disequilibrium in East Asians. Similarly, possession of C2+HLA-C in the presence of KIR AA genotype increased protection from CML (Pc=0.003). Potentially explaining these genetic results, NK cells from KIR AA individuals were significantly more cytotoxic towards primary leukemic cells than those from individuals with other KIR genotypes (P<0.0001). The KIR allotypes encoded by East Asian KIR A haplotypes are known to be strongly inhibitory, arming NK cells to respond vigorously to leukemia cells. Thus, the study of populations with distinct KIR haplotype distributions can enlighten understanding of immune mechanisms that significantly impact disease pathogenesis.